Bluefin tuna larval rearing and development: State of the art - Kaji T. (Domestication of the bluefin tuna Thunnus thynnus thynnus, 2003)
In Japan, trials for mass seed production of Pacific bluefin tuna, Thunnus thynnus, have been conducted vigorously in recent years. There are three major problems concerning seed production: (i) early mortality during the first 10 days after hatching; (ii) cannibalism around 20 days after hatching; and (iii) collisions against the tank wall observed from juvenile period. Studies on the developmental biology of bluefin tuna larvae have been published intensively over the past years, using laboratory-reared specimens. Developmental characteristics of bluefin tuna are summarized in the second part of the present paper.
1. International Symposium on Domestication of the Bluefin Tuna Thunnus Thynnus Thynnus, 2002/02/03-08, Cartagena (Spain)